AN EVALUATION OF THE 2013 CURRICULUM ASSISTANCE TRAINING PROGRAM FOR HISTORY TEACHERS IN PEKANBARU - Isjoni Isjoni (Education Administration Study Program, School of Postgraduate Studies, Universitas Riau, 2019)
This study is aimed at measuring the effectiveness of the 2013 Curriculum implementation assistance training program for school principals and History teachers conducted by the education office in Pekanbaru City. The study was conducted using the CIPP (Context, Input, Process, and Product) evaluation model introduced by Stufflebeam (2003). The data were collected through interviews, documentation, and observation. The subject of the study was the Pekanbaru city education office. The results show that the evaluation of the 2013 Curriculum implementation assistance training program resulted in a background, goals, objectives, expected results, and legal basis; the Input Evaluation resulted in criteria for training participants, training preparation programs, companion criteria, training organizers, training facilities, mentoring strategies, mentoring patterns, mentoring training mechanisms, training manuals, training implementation schedules, and training funding; The process evaluation resulted in the implementation of mentoring preparation, program structure readiness, teaching material readiness, preparedness of assistant staff, readiness of organizers, and readiness of training facilities which became the foundation of the committee to carry out the training. Furthermore, the assistants carry out the learning process; Product evaluations produce training graduates' competency standards, the level of success of training participants, and the impact of training graduates. From the evaluation results, the context obtained a value of 4.96 in the Very Good category. While the process evaluation obtained an average of 2.6 Poor categories and product evaluations obtained a score of 2.80 Poor category. Overall, the evaluation component of the K13 mentoring training program for history subjects at the Pekanbaru City High School scores 3.7 in the Good category. This means that the implementation of the K13 mentoring training program for history subjects at the Pekanbaru City High School is at a good level.